2012
DOI: 10.1002/j.0022-0337.2012.76.5.tb05285.x
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Student Diversity in Dental Schools: A Model That Works

Abstract: It is well known that there is a large disparity between the proportions of African Americans, Hispanics, and American

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 9 publications
0
45
0
Order By: Relevance
“…The study found that strategic outreach to underrepresented populations and changing admissions procedures were commonly used approaches among participating schools, which resulted in an increase in applications from and enrollment of underrepresented minority students at all fifteen participating institutions (Brunson, 2010;RWJF, 2009RWJF, & 2013. Institutional level case studies of holistic admissions models also support the idea that restructuring admissions to be more holistic was useful in recruiting and admitting more racial and ethnic minorities (Brunson, 2010;Lacy, 2012).…”
Section: Overview Of Findingsmentioning
confidence: 80%
See 2 more Smart Citations
“…The study found that strategic outreach to underrepresented populations and changing admissions procedures were commonly used approaches among participating schools, which resulted in an increase in applications from and enrollment of underrepresented minority students at all fifteen participating institutions (Brunson, 2010;RWJF, 2009RWJF, & 2013. Institutional level case studies of holistic admissions models also support the idea that restructuring admissions to be more holistic was useful in recruiting and admitting more racial and ethnic minorities (Brunson, 2010;Lacy, 2012).…”
Section: Overview Of Findingsmentioning
confidence: 80%
“…Targeted recruitment  Deliberate recruitment activities help programs meet diversity goals in health profession graduate programs (Cahn, 2015)  URM specific recruiters correlated with higher URM student enrollment in PA programs (DiBaise, et al, 2015)*  Comprehensive, targeted, recruitment and admissions program led to higher than average enrollment of URM students into dental school (Lacy, et al, 2012) Bridge to Dentistry at TAMHSC Baylor College of Dentistry…”
Section: Type Of Program Evidence For Effectiveness Of Program Type Ementioning
confidence: 99%
See 1 more Smart Citation
“…After title and abstract screening, 29 publications that did not answer the focused question or were duplicates were excluded. In total 18 articles were sought, including nine articles [ 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] discussing workforce diversity in dentistry ( Table 1 ); and nine articles [ 1 , 2 , 8 , 9 , 10 , 22 , 23 , 24 , 25 ] discussing licensing process for foreign-trained dentists ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Disparity between the proportions of African Americans, Hispanics and American Indians in the general U.S. population and the nation’s dental profession, has been extensively reported in the literature [ 7 , 19 ]. These minority groups represent approximately 30% of U.S. population; however, only comprise 6% of the dental workforce [ 15 , 17 ]. In the year 2016, foreign-trained dentists working outside academic settings represented 5.6% of the U.S. dental workforce [ 25 ].…”
Section: Resultsmentioning
confidence: 99%